practical and theoritical analysis of shared appreciation mortgage - Gao, Yang (2007)
This dissertation examines the current development of shared appreciation mortgage (SAM) that allows the borrower pays the lower interest rate than that of fixed-rate mortgage, in exchange the lender requires a share of the house price appreciation when the house is sold or the loan is refinanced. Meanwhile, the design of the model to price SAM will be given as SAM can be considered as the nearly default-risk free mortgage and a combination of credit facility and an American call option. Finally, I found that the failure to widely use SAM is attributed to the limitation of SAM, the absence of secondary market, the legal and structural impediments and the issue of moral hazard. In addition, some potential drawbacks of SAM can lead to the parameters that calculated the components in the SAM contact inaccurate. Therefore, SAM could be developed more rapidly if the potential drawback can be resolved in the first place.